1985
DOI: 10.1111/j.1476-5381.1985.tb10563.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolongation of inhibitory postsynaptic currents by pentobarbitone, halothane and ketamine in CA1 pyramidal cells in rat hippocampus

Abstract: Spontaneous inhibitory postsynaptic currents (i.p.s.cs) were recorded in voltage‐clamped CA1 neurones in rat hippocampal slices. The exponential decay of i.p.s.cs was prolonged by concentrations of sodium pentobarbitone as low as 50 μM. With concentrations up to 100 μM, there was no change in the amplitude or rise time of the currents but current amplitude was depressed at 200 μM. The prolongation of currents increased with drug concentration within the range tested (50 to 200 μM). Halothane, at concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
70
2
4

Year Published

1986
1986
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(83 citation statements)
references
References 33 publications
7
70
2
4
Order By: Relevance
“…Using this approach to study pharmacological modulation of the GABA A receptor, it has been proposed that barbiturates alter transition rates between agonist-bound closed states (Macdonald et al, 1989a;Macdonald and Olsen, 1994), neurosteroids decrease the exit rate from the desensitized state of the receptor (Zhu and Vicini, 1997), and benzodiazepines increase the agonist binding rate (Rogers et al, 1994) or decrease agonist unbinding rate and accelerate desensitization (Mellor and Randall, 1997). In addition, it has been proposed that dephosphorylation of the GABA A receptor reduces the agonist unbinding rate, slowing deactivation and prolonging inhibitory currents (Jones and Westbrook, 1997).The volatile anesthetic halothane prolongs GABA A receptormediated IPSCs (Gage and Robertson, 1985;Mody et al, 1991;Jones and Harrison, 1993;Pearce, 1996), as do a great number of intravenous and other volatile anesthetic agents (Zimmerman et al, 1994). It is becoming widely accepted that this effect contributes importantly to the production of "anesthesia" (Tanelian et al, 1993;Franks and Lieb, 1994).…”
mentioning
confidence: 99%
“…Using this approach to study pharmacological modulation of the GABA A receptor, it has been proposed that barbiturates alter transition rates between agonist-bound closed states (Macdonald et al, 1989a;Macdonald and Olsen, 1994), neurosteroids decrease the exit rate from the desensitized state of the receptor (Zhu and Vicini, 1997), and benzodiazepines increase the agonist binding rate (Rogers et al, 1994) or decrease agonist unbinding rate and accelerate desensitization (Mellor and Randall, 1997). In addition, it has been proposed that dephosphorylation of the GABA A receptor reduces the agonist unbinding rate, slowing deactivation and prolonging inhibitory currents (Jones and Westbrook, 1997).The volatile anesthetic halothane prolongs GABA A receptormediated IPSCs (Gage and Robertson, 1985;Mody et al, 1991;Jones and Harrison, 1993;Pearce, 1996), as do a great number of intravenous and other volatile anesthetic agents (Zimmerman et al, 1994). It is becoming widely accepted that this effect contributes importantly to the production of "anesthesia" (Tanelian et al, 1993;Franks and Lieb, 1994).…”
mentioning
confidence: 99%
“…GABA-mediated IPSCs play a crucial role in neuronal processing, and changes in their kinetics, like those generated by widely used drugs (Gage and Robertson, 1985;Harrison et al, 1987;Otis and Mody, 1992), result in important therapeutic effects.…”
mentioning
confidence: 99%
“…Studies from PET and electrophysiology indicated that in some brain regions, such as thalamus, hippocampus, inhalation anesthetic agents induced changes in glucose metabolic rate or postsynaptic potential (Gage and Robertson, 1985;Alkire et al, 2000), where anesthetic actions in these brain regions are known occur. However, there is still no morphological evidence about the functional targets of these inhalation anesthetic.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that sevoflurane exposure can activate GABAergic neurons as indicated by nuclei Fos expression, thus enhance inhibitory effect on neuronal transmission. This is considered to be a mechanism for sevoflurane anesthesia and has obtained its electrophysiological evidences (Gage and Robertson, 1985). Eletrophysiological studies demonstrate that inhibitory GABAergic neuron activity is enhanced by inhaled anesthetics, suggesting a mechanism by which sevoflurane induces anesthesia.…”
mentioning
confidence: 99%